2019
DOI: 10.1093/glycob/cwz090
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent bioactivity of versican fragments

Abstract: Versican (VCAN) proteolysis and the accumulation of VCAN fragments occur in many developmental and disease processes, affecting extracellular matrix (ECM) structure and cell phenotype. Little is known about the significance of proteolysis and the roles of fragments, or how this ECM remodeling affects the microenvironment and phenotype of diseased cells. G1-DPEAAE fragments promote aspects of epithelial–mesenchymal transitioning in developing and diseased cells, resulting in cell migration. Enhanced proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 95 publications
1
14
0
Order By: Relevance
“…In addition, a recent study (187) using bone marrow biopsies from 35 myeloma patients revealed a significant correlation of versikine accumulation with infiltration of CD8+ T cells supporting a model in which macrophages and regulatory DCs secrete tolerogenic versican which is subsequently degraded, generating versikine and further altering the immunosuppressive nature of the tumor microenvironment. Thus, taken together, these studies establish that both intact versican and a proteolytic degradation product of versican have immunomodulatory properties and suggest that the anti-tumor properties of versikine might antagonize the protumor properties of intact versican (13,23,73,75,188). The juxtaposition of these findings indicates that the consequences of ECM-derived-DAMP interactions with PRRs can have sharply differing outcomes depending on the contextual specifics of versican structure.…”
Section: Versican and Inflammation In Cancer: Pro-and/or Anti-inflammmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, a recent study (187) using bone marrow biopsies from 35 myeloma patients revealed a significant correlation of versikine accumulation with infiltration of CD8+ T cells supporting a model in which macrophages and regulatory DCs secrete tolerogenic versican which is subsequently degraded, generating versikine and further altering the immunosuppressive nature of the tumor microenvironment. Thus, taken together, these studies establish that both intact versican and a proteolytic degradation product of versican have immunomodulatory properties and suggest that the anti-tumor properties of versikine might antagonize the protumor properties of intact versican (13,23,73,75,188). The juxtaposition of these findings indicates that the consequences of ECM-derived-DAMP interactions with PRRs can have sharply differing outcomes depending on the contextual specifics of versican structure.…”
Section: Versican and Inflammation In Cancer: Pro-and/or Anti-inflammmentioning
confidence: 74%
“…The degradation of versican is affected by several different families of proteases that increase during inflammation. Such proteases include matrix metalloproteinases (MMPs), i.e., MMP-1,−2,−3,−7, and−9 (64-66), serine protease plasmin (67), and at least five ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) MMPs, specifically ADAMTS-1,−4,−5,−9, and−20 [see reviews (12,13,(68)(69)(70)]. Cleavage of versican by ADAMTS-1,−4,−5, and−9 leads to production of an amino-terminal fragment, termed versikine, that can be detected using an antibody recognizing the neoepitope sequence DPEAAE (DPE) (12,71,72).…”
Section: Versicanmentioning
confidence: 99%
See 2 more Smart Citations
“…89 The examples are endostatin from type XVIII collagen, tumstatin from type IV collagen, and endorepellin from perlecan. 90 There are an increasing number of reports demonstrating the biological function of the N-terminal fragment of Vcan, 91 termed "versikine." Combined knockout mice of ADAMTS-5, ADAMTS-9, and ADAMTS-20 genes exhibit syndactyly due to impaired apoptosis by an accumulation of Vcan, and local treatment with versikine rescues the phenotype, indicating that versikine leads to cellular apoptosis.…”
Section: Functional Vcan Fragment As Versikinementioning
confidence: 99%